Dietary proteins, amino acids and insulin resistance: a mini review - Coker, Melynda S.; Coker, Robert H. (Frontiers in Nutrition, 2025)
The influence of protein intake on insulin resistance, has garnered an increasing amount of interest over the past few decades. Increased provisions of dietary protein during weight loss helps preserve skeletal muscle, which as the largest organ in the human body, is responsible for 80% of insulin-stimulated glucose disposal. The postprandial influence of essential amino acids (EAAs) either alone or as part of intact proteins are regulated through leucine-induced activation of mammalian target of rapamycin (mTOR) that serves to promote muscle protein synthesis and maintain skeletal muscle. High protein diets and/or EAA supplementation have also been demonstrated to improve satiety and augment mitochondrial function, which may have an indirect or direct influence on insulin sensitivity. On the other hand, chronic elevations in postabsorptive concentrations of branched chains amino acids (BCAAs) have been associated with chronic activation of the mTOR pathway, impairing insulin action. It appears that causal links between BCAAs and the pathogenesis of insulin resistance are reliant on chronic hyperinsulinemia and nutrient overload that foster chronic lipotoxicity. Conversely, postprandial elevations in EAAs leverage sensing as an anabolic mediator to facilitate muscle remodeling, augment satiety and improve metabolic regulation.